STABILISASI ANTOSIANIN BERAS HITAM (Oryza sativa, L. indica) DENGAN KOPIGMENTASI DAN ENKAPSULASI - , FIAMETTA AYU PURWANDARI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Black rice (Oryza sativa L. indica) is one of cereal comodities consider as source of anthocyanin. One of the obstacle of using anthocyanins as food colorant is their low stability. Copigmentation and encapsulation can enhance the color stability of anthocyanin. Flavonoid extract obtained from bilimbi leaves (Averrhoa bilimbi) and sow thistle leaves (Sonchus arvensis) were used as copigment. Study the color characteristic of anthocyanin was investigated in buffer pH 1-7, anthocyanin content and total flavonoid was measured using pH-differential method and AlCl3 spectrophotometric respectively, the copigmentation effect was observed from bathochromic and hyperchromic shift. Degradation rate constant and half-time was obtained from anthocyanin content, color change of encapsulated and absorbance of encapsulated anthocyanin in buffer pH 3 was also measured during storage. Anthocyanin content of black rice was 105,11±7,76 mg/100g (db). Color characteristic from black rice anthocyanin was greatly influenced by pH. Total flavonoid of bilimbi leaves and sow thistle leaves extract was 2,17±0,15% mg extract and 1,18±0,05% mg extract respectively. Purification increased the total flavonoid content of bilimbi leaves and sow thistle leaves extract to 2,75±0,15% mg extract and 1,52±0,04% mg extract respectively. Flavonoid extract can be used as copigment and show copigmentation effect as batochromic and hipercromic at pH 1 and 3. Copigment significantly lowered the degradation rate of anthocyanin and extended its half-time. Combination copigmentation and encapsulation decreased color loss due to photooxidation and thermal significantly.